Implementation of the Curriculum at SD Muhammadiyah Special Program Kottabarat Surakarta to Develop Multiple Intelligences in Its Students - Yanti, Nila Dwi; Utomo, Arief Cahyo (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to 1) understand the implementation of the curriculum at SD Muhammadiyah Program Khusus Kottabarat Surakarta to develop the multiple intelligences of its students, 2) to understand the results or impacts of the implementation on the development of multiple intelligences in the students of SD Muhammadiyah Program Khusus Kottabarat Surakarta, 3) to identify the obstacles in the implementation of the curriculum at SD Mu-hammadiyah Program Khusus Kottabarat Surakarta. Methodology: This research uses a descriptive qualitative approach with a case study design and literature review, employing techniques such as observation, interviews, and documentation. Results: The results of the study indicate that every child has potential that can be maximally developed through the learning and habituation process, integra-ting religious values sourced from the Qur'an and Hadith. The flagship pro-grams of SD Muhammadiyah Program Khusus Kottabarat Surakarta include school culture programs, character culture programs, weekday extracurricu-lars, and weekend extracurriculars, which aim to develop and optimize stu-dents' multiple intelligences in accordance with their individual potentials. Applications/Originality/Value: This research provides novelty in understanding the implementation of the national curriculum and the sharia school curriculum. At SD Muhammadi-yah Program Khusus Kottabarat Surakarta, the novelty lies in the integrated approach that systematically combines academic education with Islamic val-ues to balance general knowledge, character, and spirituality in elementary school students. Through the application of the sharia school curriculum, it can strengthen children's Islamic character, making it relevant for the holis-tic development of multiple intelligences and children's character.